إجماعات ابن رشد الحفيد من خلال كتاب بدايةالمجتهد ونهاية المقتصد كتاب الحج أنمىذجا - مدخل, حمزة; ضمايدة, عبد الكريم; يعقوب, العربي (University of Eloued-جامعة الوادي, 2015)
The Summary - This dissertation is a complementary thesis to obtain a bachelor degree in Islamic sciences prepared by the students whose names follow : Larbi Yagoub, Hamza Medekhel and Abdelkarim Demaida , the University of Echahid Hamma Lakhdar, Faculty of Social and Human Sciences , department of Islamic Sciences Branch of Islamic Sciences. It is entitled by : The Consensuses of Ibn Rushd the Grandchild in his book Badyatou Elmoujtahid wa Nehayatou Elmoktasid ( The Beginning of the ا Assiduous and the Close of the Saver) , the chapter of pilgrimage as a model. يولدا يلة كThe project is divided , into an introduction , two themes and conclusion. The first theme : Defining the author and the book , and mentioning some questions about the consensus.The second chapter : The practical part , where we studied the authentication of the consensuses mentioned by Ibn Ruchd in the chapter of pilgrimage of the above book.The Conclusion : We concluded in different results: the prominent one is that most of Ibn Rushd Consensuses in the pilgrimage chapter are precise and constant and rarely to find controversy in.
مذكرة ليسانس
Keywords: اجماعات/ابن رشدالحفيد/المجتهد ونهاية المقتصد; Consensus/Ibn Rushd al-Hafid/Al-Mujtahid et Nihayat al-Muqtasid